Studi Penggunaan Antihipertensi Golongan Calcium Channel Blocker pada Pasien Stroke Iskemik - Anita Tria Amanda; Nailis Syifa; Didik Hasmono; Rani Nur Badriyah (Jurnal Riset Farmasi, 2025)
Abstract. Ischemic stroke is a leading cause of disability and death in Indonesia, with hypertension as the biggest risk factor. Blood pressure control is key to therapy, one of which is through the use of Calcium Channel Blockers (CCBs) that work by arterial vasodilation. This study aims to determine the pattern of CCB use in ischemic stroke patients at Dr. Saiful Anwar Regional Hospital, including drug type, dose, route, frequency, duration of therapy (>3 days), and length of hospitalization (>7 days). The study used a retrospective descriptive design based on medical records data from 2024. The results showed Amlodipine (1 × 10 mg) po as the most common single therapy (71 patients; 40%). Combinations of two drugs, such as Amlodipine and Valsartan, were used in 23 patients (15%), while combinations of three and four drugs were used in 6 (3%) and 2 patients (1%), respectively. In addition, there were 73 cases (41%) of regimen changes during treatment. These findings emphasize the importance of adjusting antihypertensive therapy based on clinical conditions and evaluating the rationality of drug use to improve therapeutic outcomes. Abstrak. Stroke iskemik merupakan penyebab utama kecacatan dan kematian di Indonesia, dengan hipertensi sebagai faktor risiko terbesar. Pengendalian tekanan darah menjadi kunci terapi, salah satunya melalui penggunaan Calcium Channel Blocker (CCB) yang bekerja dengan vasodilatasi arteri. Penelitian ini bertujuan mengetahui pola penggunaan CCB pada pasien stroke iskemik di RSUD Dr. Saiful Anwar, meliputi jenis obat, dosis, rute, frekuensi, durasi terapi (>3 hari), serta lama rawat inap (>7 hari). Penelitian menggunakan desain deskriptif retrospektif berdasarkan data rekam medis tahun 2024. Hasil menunjukkan Amlodipin (1 × 10 mg) po sebagai terapi tunggal terbanyak (71 pasien; 40%). Kombinasi dua obat, seperti Amlodipin dan Valsartan, digunakan pada 23 pasien (15%), sedangkan kombinasi tiga dan empat obat pada 6 (3%) dan 2 pasien (1%). Selain itu, terdapat 73 kasus (41%) perubahan regimen selama perawatan. Temuan ini menegaskan pentingnya penyesuaian terapi antihipertensi berdasarkan kondisi klinis serta evaluasi rasionalitas penggunaan obat untuk meningkatkan luaran terapi.